PRODUK ASING DAN PRODUK LOKAL PADA PERDAGANGAN ELEKTRONIK LINTAS BATAS: SEBUAH KERANGKA KONSEPTUAL - Dwi Kartikasari; Muhamad Nabil Almunawar; Muhammad Anshari Ali; Wardah Hakimah binti Hj Sumardi (Faculty of Economics and Business University of Lampung, 2023)
We aim to add value to the ongoing inconsistencies by extracting models from past studies and building an overarching framework for understanding the purchase intentions of foreign and domestic products in the cross-border electronic commerce (CBEC) context. We review significant works in various disciplines and systematically extend abstractions from diverse models and theories toward iterative methods. We deconstruct and (re)construct them into the framework. We identify the importance of segmenting consumer engagement with global-local discourses and screen samples not engaging with the country of origin (COO) discussions. We pinpoint the significance of the underlying theories of social class, rational choice, social identity, COO, substitute versus complementary, schema, consumer culture, adaptive structuration, and the unified theory of acceptance and use of technology. We highlight the urgency of drawing from multidisciplinary approaches to acknowledge the complex relationship between constructs of product types, social class, ethnocentrism, informedness, benefits, perceived risks, and the purchase intention of domestic and foreign products. Researchers should refine models based on consumer segments and test the framework to examine its usability. Policymakers and international marketers can refine policies and strategies by incorporating the framework's critical success factors. We fill the wide research gap in international marketing and information systems literature by offering an integrative approach that broadens our understanding of foreign versus domestic product controversies.